Effects of electroacupuncture on pediatric chronic urinary retention: a case-series study - Min Yang; Shuai Gao; Hao Yao; Hao Yao; Xin He; Xin He; Jiufei Fang; Yu Chen; Zhishun Liu (Frontiers Media S.A., 2023)
ObjectivesThis study aims to preliminarily evaluate the effect and safety of electroacupuncture (EA) in treating pediatric chronic urinary retention (CUR) following lumbosacral surgeries, with treatment duration evaluated.MethodsThis prospective case-series study was performed from August 5, 2017, to July 31, 2022. Pediatric patients diagnosed with CUR following lumbosacral surgeries were included and treated by EA for 2-16 weeks. Responders were defined as participants achieving a reduction of 50% or more in post void residuals (PVR) from baseline. Time-to-event analysis was applied to explore the association between EA treatment duration and response rate. Adverse event was recorded.ResultsTotally 14 participants (mean [SD] age, 12 [4] years) completed EA treatment. Response rate was 71% (10/14) at the 12th week. 50% (7/14) of participants removed catheters at the 12th week, and none of them experienced re-catheterization in the 24-week follow-up. No serious adverse event was reported. Time-to-event analysis estimated that over 50% patients could respond to EA of more than 8 weeks. Subgroup analysis showed that participants with baseline PVR ≥300 ml and CUR duration ≥12 months experienced longer EA duration to reach the response rate of 50%, compared with those whose PVR <300 ml and CUR duration <12 months (median value: 12 weeks vs. 8 weeks, 12 weeks vs. 4 weeks, respectively).ConclusionsEA could reduce PVR for pediatric patients suffering from CUR following lumbosacral surgeries, with long-term efficacy and safety. EA treatment of more than 8 weeks was reasonable. Further study of a larger sample and controlling is needed.Clinical Trial Registrationwww.chictr.org.cn, identifier, ChiCTR1800020222.